Contribution of Foreign Aid to GDP in Nepal - Dangal, Dil Nath; Chapagai, Shiva Dutta; Ghimire, Krishna Prasad (Economic Review of Nepal, 2024)
The objective of this study is to examine how foreign aid has influenced Nepal’s Gross Domestic. It employs a causal-comparative research design to analyze the effect of foreign aid on Nepal’s GDP based on panel data covering from 2000/2001 to 2020/2023. By applying the Ordinary Least Square (OLS) regression and correlation coefficient to estimate the relationships between GDP and foreign aid empirically. The study reveals that the p-value associated with this analysis is less than 0.05 indicating that the relationship between foreign aid- encompassing both grants and loans and GDP is statistically significant. Foreign aid to GDP ratio fluctuates between 3.2% to 9.32%. Despite its significant impact, the study also highlights fluctuations in GDP foreign aid, indicating economic challenges. The results suggest that although foreign aid is vital for economic stability and growth, the findings also indicate that while foreign aid is crucial for Nepal’s economic well-being, the country needs to focus on long-term self-sufficiency and sustainable development strategies to reduce reliance on foreign aid. The study emphasizes the complex improvement of governance and strategic planning to maximize the benefits of foreign aid.